The clinical case of effective treatment of pulmonary tuberculosis in the female adolescent after kidney transplantation - E. S. Ovsyankina; N. L. Karpina; F. G. Poluehktova; O. V. Kasimtseva; S. G. Mikhaylov; A. Eh. Ergeshov (Туберкулез и болезни лёгких, 2016)
The article presents the clinical case of successful treatment of pulmonary tuberculosis in the female adolescent with concurrent chronic kidney disease. The article highlights the need of the advanced examination for tuberculosis in patients with chronic kidney disease before and after renal transplantation and the need for integral individual approach to treatment of pulmonary tuberculosis in such patients.